1995
DOI: 10.1111/j.1432-1033.1995.687_2.x
|View full text |Cite
|
Sign up to set email alerts
|

The Uniform Galactose 4‐Sulfate Structure in the Carbohydrate‐Protein Linkage Region of Human Urinary Trypsin Inhibitor

Abstract: The carbohydrate-protein linkage region of a chondroitin 4-sulfate chain attached to urinary trypsin inhibitor (UTI) was isolated from human urine and characterized structurally. The chondroitin 4-sulfate chain was released from UTI by p-elimination using alkaline NaBH, then digested with chondroitinase ABC. These treatments resulted in only a single hexasaccharide alditol derived from the carbohydrateprotein linkage region. Chemical and enzymic analyses and 600-MHz 'H-NMR spectroscopy revealed that the hexasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 31 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Previous reports of the bikunin CS linkage region structure are based on analysis of urine and plasma that eluted from an anion exchange column with a salt gradient up to 0.5 M NaCl (1,2,43). These fractions have been reported to contain the disulfated CS linkage region hexasaccharide structure ⌬HexA␣1-3GalNAc(4S)␤1-4GlcA␤1-3Gal(4S)␤1-3Gal␤1-4Xyl-ol (24,25,44,45). The 2B6 antibody is known to react with the linkage region hexasaccharide ⌬HexA␣1-3GalNAc(4S)␤1-4GlcA␤1-3Gal␤1-3Gal␤1-4Xyl-ol (46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports of the bikunin CS linkage region structure are based on analysis of urine and plasma that eluted from an anion exchange column with a salt gradient up to 0.5 M NaCl (1,2,43). These fractions have been reported to contain the disulfated CS linkage region hexasaccharide structure ⌬HexA␣1-3GalNAc(4S)␤1-4GlcA␤1-3Gal(4S)␤1-3Gal␤1-4Xyl-ol (24,25,44,45). The 2B6 antibody is known to react with the linkage region hexasaccharide ⌬HexA␣1-3GalNAc(4S)␤1-4GlcA␤1-3Gal␤1-3Gal␤1-4Xyl-ol (46).…”
Section: Discussionmentioning
confidence: 99%
“…The CS chain linkage region of bikunin in urine and plasma has been shown to contain a disulfated hexasaccharide (24,25) on its non-reducing end, whereas other groups have suggested that the non-reducing end is monosulfated on the GalNAc residue (9,28). HC1 and HC2 are located relatively close to each other on the bikunin CS chain in I␣I with HC2 located toward the reducing end of the CS chain and HC1 located further toward the non-reducing end (26).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The linkage region of this GAG chain has been the target for several studies concluding a uniform galactose-4-sulfate tetrasaccharide structure (GlcA␤3Gal␤3(4-O-SO 3 )-Gal␤4Xyl␤-O-) in both human plasma and urinary samples (22,23). The I␣I complex is a unique macromolecular arrangement of structurally related proteins, i.e.…”
mentioning
confidence: 99%
“…Shibata et al (12) also observed that the first disaccharide repeat was mostly unsulfated, and more so if the preceding xylose was phosphorylated. From the CS-substituted trypsin inhibitors of urine and plasma (15,16), a uniformly GalNAc 4-O-sulfated and Gal 4-O-sulfated linkage region was obtained. In shark cartilage aggrecan CS, which has mainly 6-O-sulfated GalNAc, the first Gal of the linkage region and sometimes both the first and second Gal can carry 6-O-sulfate (17,18).…”
mentioning
confidence: 99%